Connection of urethral microbiota with the semen quality and the concentration of endocrine disrupters in men semen - S. V. Chigrinets; G. V. Bryuhin (Андрология и генитальная хирургия, 2018)
The study objective is to investigate the correlations between opportunistic microorganisms of the urethra and the quality of ejaculate, as well as the concentration of ubiquitory endocrine disruptors (bisphenol A and triclosan) in men semen.Materials and methods. We analysed 63 semen samples of men with normo- and patozoospermia. In seminal fluid the concentration of bisphenol A and triclosan was determined by gas chromatography with mass spectrometry. The microbiocenosis of the urethra was studied by real-time polymerase chain reaction using the Androflor test system. The results were subjected to statistical processing using the Mann — Whitney U-test and correlation analysis. A p-value less than 0.05 was considered significant.Results. Bisphenol A was found in 100 % of the semen samples. Triclosan was detected in 84.9 % of the samples. Comparison groups on the quality of ejaculate (normo- and pathozoospermia) were statistically significantly different in the concentration of bisphenol A and triclosan in seminal fluid (p <0.001) and (p = 0.003) respectively. The study established statistically significant correlations between bisphenol A concentration, seminal triclosan and urethral microbiota: Lactobacillus spp. (r = 0.501, p = 0.003), Corynebacterium spp. (r = 0.425, p = 0.015), Anaerococcus spp. (r = 0.371, p = 0.045), Eubacterium spp. (r = 0.357, p = 0.037) for bisphenol A and Staphylococrns spp. (r = 0.392, p = 0.026), Streptococcus spp. (r = —0.486, p = 0.005) for triclosan.Conclusion. In this study the connection of the urethral microbiota with the quality of the ejaculate and the concentration of endocrine dis-ruptors (bisphenol A and triclosan) in men semen was established. In this regard, it is necessary to take into account the role of asymptomatic urethral dysbiosis when administering patients with poor ejaculate quality.